Anaerobic digestion of thermal pre-treated sludge at different solids concentrations – Computation of mass-energy balance and greenhouse gas emissions. (1st July 2015) - Pilli, Sridhar; More, Tanaji; Yan, Song; Tyagi, Rajeshwar Dayal; Surampalli, Rao Y.
Abstract: The effect of thermal pre-treatment on sludge anaerobic digestion (AD) efficiency was studied at different total solids (TS) concentrations (20.0, 30.0 and 40.0 g TS/L) and digestion times (0, 5, 10, 15, 20 and 30 days) for primary, secondary and mixed wastewater sludge. Moreover, sludge pre-treatment, AD and disposal processes were evaluated based on a mass-energy balance and corresponding greenhouse gas (GHG) emissions. Mass balance revealed that the least quantity of digestate was generated by thermal pre-treated secondary sludge at 30.0 g TS/L. The net energy (energy output-energy input) and energy ratio (energy output/energy input) for thermal pre-treated sludge was greater than control in all cases. The reduced GHG emissions of 73.8 × 10 −3 g CO2 /g of total dry solids were observed for the thermal pre-treated secondary sludge at 30.0 g TS/L. Thermal pre-treatment of sludge is energetically beneficial and required less retention time compared to control. Highlights: Energy sustainability of the thermal pre-treatment and anaerobic digestion is evaluated. Energy and greenhouse gas emissions are considered as criteria in evaluating the process. Thermal pre-treatment of sludge followed by anaerobic digestion is energetically sustainable. Greenhouse gas emissions are reduced with thermal pre-treated of sludge followed by anaerobic digestion.